Coastal Erosion Monitoring Along the Coast of Negeri Sembilan, Malaysia - Mispan, Ahmad Zaidi; Mohammad Razi, Mohd Adib; Ismail , Isha Baizura; Wang Mo; Nur Farahanim Mohd Zulkifli (International Journal of Integrated Engineering, 2025)
Coastal monitoring, mapping and analysis are comprehensive for various coastal studies, such as advancement of regression planning, geohazard identification, decomposition- enhancing research, and theoretical or predictive modelling or coastal characterization. The objectives of this research were to identify the overview of coastal erosion monitoring along the coast of Negeri Sembilan, Malaysia. The coastal erosion assessment approach includes the creation of sediment cells for the coastal area, as well as the collecting and examination of secondary data related to the research areas. Categorization of erosion has been concluded based on locations of study area. Category 1 erosion was discovered along the coastline at the PD Waterfront, Batu 1, Jalan Pantai Port Dickson, The Regency Tanjung Tuan Beach Resort (Batu 5), Tanjung Gemok, Kampung Gelam, and Pantai Teluk Kemang (Batu 8). Pantai Tanjung Gemok, a prominent recreational beach, is currently experiencing groyne erosion downdrift. Apart from that, a groyne is being eroded downdrift in Pantai Regency Batu 5, Negeri Sembilan.